Kompetensi Manajerial Kepala Madrasah Dalam Mengimplementasikan Program Pengembangan Keprofesian Berkelanjutan Guru Era Digital - Rohmawati, Zidny Nur (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2023)
Teacher development is an important component in educational institutions. This is because the teacher is one of the potential resources that affect the quality of students and the achievement of educational goals. In an increasingly rapid pace of development, madrasa heads as managers of educational institutions are required to be able to manage existing human resources (HR). As an effort to improve teacher competence, especially in the pedagogic and professional dimensions, the teacher continuous professional development (CPD) program is a means for teachers to develop their competence and knowledge. Thus, it is necessary to have the role of the madrasa head in involving teachers in the PKB program. The research focuses raised in this study are: 1) How is the head of madrasah in planning the sustainable professional development program for digital era teachers at MAN 2 Malang City; 2) How is the madrasa principal in implementing the digital era teacher continuous professional development program at MAN 2 Malang City; 3) How is the implementation of the digital era teacher sustainable professional development program at MAN 2 Malang City. This study uses a descriptive qualitative approach, where the researcher describes the research findings which are unique in the field. To obtain data related to the managerial competence of the madrasah principal in implementing the CPD program, data collection techniques were carried out in the form of observation, interviews and documentation. The data that has been collected will be analyzed using data reduction, data presentation and drawing conclusions. Based on the results of the study, it can be concluded that: 1) CPD program planning is carried out on: a) the madrasah annual work meeting agenda; and b) in the MGMP professional organization. The planning carried out is based on three aspects, including: a) the times; b) madrasa vision and mission; and c) reports on the results of supervision. 2) The implementation of the PKB program consists of three components, including: a) self-development; b) scientific publications; c) innovative work. In implementing the CPD program, the role of the madrasa head as manager is as follows: a) placing teachers according to academic qualifications; b) directing teachers in development programs; c) formulating and setting educator standards; d) socialize and motivate teachers to participate in the CPD program; 3) The results of the implementation of the CPD program, including: a) Increasing the pedagogic and professional competence of teachers; b) Increasing student academic achievement.